Capital Expenditure Analysis In District And City Province Of Central Java - Anna Sofia Atichasari; Rida Ristiyana (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
The demands of public accountability and transparency make local governments have to be able to optimize capital expenditures to improve public services and increase economic productivity, so that equitable development can be successful both at the center and the regions. The motivation of the research is to analyze capital expenditure in terms of the level of economic growth, regional revenue allocation, general allocation funds, special allocation funds, value for money (economical, efficient, effective). The type of causality and descriptive approach involves 29 districts and 6 cities in Central Java province for the 2014-2019 period using purposive sampling so that the number of observation data (n) = 210. The analysis technique uses panel data regression. The results of the study found that the level of economic growth had a negative and significant impact on capital expenditures for the allocation of local revenue, general allocation funds, special allocation funds had a positive and significant impact on capital expenditures. Economical has no impact on capital expenditures. Efficient and has a negative impact on capital expenditures. Ratio analysis shows economic performance; efficient ratio indicates efficient performance and effective ratio indicates ineffective performance.